NeX
45

# Voici quelques équations : a) 4x+3=3x - 5 ; b) -2x+7 = 3x-13 c) -3x+4=6x+5 d) 4-7x= -3x+1 e) 3 (x-8)=4x+5 f) -4(2+x) = 3x-5 g) 9(2-2x)= - (7x+1) h) -3 (4+x) + 3x = 6(x+1) i) 2(-5x+3) + 7(3x-1)=0 j) 5(4x+3) + 2(x+6) = 3(x+8)

(2) Réponses
waassila

h) -3 (4+x) + 3x = 6(x+1)  i) 2(-5x+3) + 7(3x-1)=0 j) 5(4x+3) + 2(x+6) = 3(x+8)a) 4x+3=3x - 5  4x-3x=-5-3 x=-8 b) -2x+7 = 3x-13 -2x-3x=-13-7 -5x=-20 x=-20/-5 x=4 c) -3x+4=6x+5 -3x-6x=5-4 -9x=1 x=1/-9 x=-1/9 d) 4-7x= -3x+1  -7x+3x=1-4 -4x=-3 x=-3/-4 x=3/4 e) 3 (x-8)=4x+5 3*x+3*(-8)=4x+5 3x-24=4x+5 3x-4x=5+24 -x=29 x=-29 f) -4(2+x) = 3x-5 -4*2-4*x=3x-5 -8-4x=3x-5 -4x-3x=-5+8 -7x=3 x=3/-7 x=-3/7 g) 9(2-2x)= - (7x+1) 9*2+9*(-2x)=-7x-1 18-18x=-7x-1 -18x+7x=-1-18 -11x=-19 x=-19/-11 x=19/11 h) -3 (4+x) + 3x = 6(x+1)  -3*4-3*x+3x=6*x+6*1 -12-3x+3x=6x+6 -6x=6+12 -6x=18 x=18/-6 x=-3 i) 2(-5x+3) + 7(3x-1)=0 2*(-5x)+2*3+7*3x+7*1=0 -10x+6+21x+7=0 -10x+21x=-7-6 11x=-13 x=-13/11 j) 5(4x+3) + 2(x+6) = 3(x+8) 5*4x+5*3+2*x+2*6=3*x+3*8 20x+15+2x+12=3x+24 20x+2x-3x=24-15-12 19x=-3 x=-3/19

caroline974181

a) 4x + 3 = 3x - 5 4x - 3x = -3 - 5 x = -8 b) -2x + 7 = 3x - 13 - 2x - 3x = - 7 - 13 -5x = -20 x = 20/5 x = 4 c) -3x + 4 = 6x + 5 -3x -6x = -4 + 5 -9x = 1 x = -1/9 x = -0,11 d) 4 - 7x = -3x + 1 4 - 1 = 7x - 3x 3 = 4x 4x = 3 x = 3/4 x = 0,75 e) 3 (x - 8) = 4x + 5 3x - 24 = 4x + 5 3x - 4x = 24 + 5 -x = 29 x = -29 f) -4(2 + x) = 3x - 5 -8 - 4x = 3x - 5 -4x - 3x = 8 - 5 -7x = 3 x = -3/7 x = -0,43 g) 9(2 - 2x) = - (7x + 1) 18 - 18x = -7x - 1 -18x + 7x = -18 - 1 -11x = -19 x = 19/11 x = 1,72 h) -3 (4 + x) + 3x = 6(x + 1) -12 - 3x + 3x = 6x + 6 -3x + 3 - 6x = +12 + 6 -6x = -18 x = -18/6 x = -3 i) 2(-5x + 3) + 7(3x - 1) = 0 -10x + 6 + 21x - 7 = 0 -10x + 21x = - 6 + 7 11x = 1 x = 1/11 x = 0,09 j) 5(4x + 3) + 2(x + 6) = 3(x + 8) 20x + 15 + 2x +12 = 3x + 24 20x + 2x - 3x = -15 - 12 + 24 22x - 3x = - 27 + 24 19x = - 3 x = -3/19 x = - 0,157

Ajouter une réponse